Application Of Selected Marine Microalgae In Thermoplastic Starch Production - Puspanadan, Soopna A/p (2021)
Starch is increasingly used in many industrial applications and as a renewable energy resource. In this study, ten indigenous microalgae (freshwater and marine) were cultured and analyzed for their biochemical content. The results showed that Chlorella salina contained the highest starch of 4.92±0.33%, followed by Spirulina sp. (2.58±1.18%). Thus, C. salina and Spirulina sp. were selected to study the effects of physical and chemical factors on their starch production. C. salina produced a higher starch yield compared to Spirulina sp., (69.46 mg/L and 16.13 mg/L respectively), under optimum growth conditions of 32 ℃, red wavelength, 24L:0D (photoperiod) and 39 ppt (salinity), hence, C. salina was selected for further investigation (chemical factors). On the other hand, the efficiency of different starch extractions methods indicated that the ethanol boiling method (0.46g starch/g freezedry biomass) was significantly better than the four other methods (ultrasonic liquid shear, hotwater bath, alkaline cell lysis and bead vortexing) used. In addition, the highest and the lowest starch yield of 46.4% and 12.8% were obtained by the ethanol boiling method and alkaline cell lysis method, respectively. Thermoplastic starch (TPS) film preparation was developed using the casting technique. Thermogravimetric analysis indicated that commercial corn starch (CS) film showed higher mass loss (81.24%) compared with the algae starch (AS) film (76.53%) and melting temperatures differential scanning calorimetry (DSC) were observed to be the highest for AS film at 320.24 ℃ whereas CS showed the lowest at 317.91 ℃.